Keanekaragaman Tumbuhan Di Hutan Suaka Margasatwa Kateri Kabupaten Malaka Plant Diversity In Kateri Wildlife Forest Malaka Regency - Marlenci Erni Seran; Arnold Ch Hendrik; Apriliana Ballo (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2025)
The cattery wildlife sanctuary is one of the conservation areas which is administratively located between two regencies, namely Malaka Regency and North Central Timor Regency (TTU).The purpose of this research is to find out Plant Diversity in the Kateri Wildlife Sanctuary Forest, Malaka Regency.The method used is the quadratic plot. Data analysis using descriptive quantitative and compositionthe type of Plant declared based on observations as well as measuring and calculating the diversity index of density, frequency, and dominance. The results showed that 13 families were found including Fabaceae, Moraceae, Rhamnaceae, Arecaceae, Lamiaceae, Apocynaceae, Anacardiaceae, Euphorbiace, Sapindaceae, Mimosaceae, Palmae/Arecales, Leguminosae, Meliaceae, and 14 species. plants includingT.Indica L., F. Benjamin L., Z. Mauritiana Lam., C. utan, T. grandis L., G. arborea Roxb., A. scholaris L., S. pinnata, A. moluccana L., S. oleosa Merr., L. leucocephalaLam. de W., A. catechu., S.grandifloraL., S. macrophyllaKing. The highest seedling density (K) was found inC. utan 0.17 ind/m2 and relative density (KR) 30.00 %. The highest K stake is found in plant T. grandis Linn. F(0.12eng/m2 and KR 61.11%. The highest tree K is found in plantA. moluccana 0.01 ind/m2 and KR 18.39%. The highest seedling frequency (F) wasplantT. grandis Linn. F 1.00 ind/m2 and relative frequency (FR) 26.32%. The highest stake F is at plantT. grandis Linn. F 1.00 ind/m2 and FR 27.78%. F the tallest tree is on plants T. Indica L. and T. grandis Linn. F 1.00 ind/m2 and FR 26.32%. The dominance (D) of the highest seedling wason plantsT. grandis Linn. F 0.08 ind/m2 and Relative dominance (DO) 21.62%. D stake there is on plants Areca catechu L. 0.17 ind/m2 and DO (24.57%). D the tallest tree is on plantsC.utan 15.05 ind/m2 and DO 25.80%.The value of the diversity index (H') of Plant typesThe results obtained are in the low to moderate category with each category being station 1 medium, station 2 medium, station 3 moderate, station 4 moderate, station 5 (ow-medium and station 6 medium.